2017
DOI: 10.2967/jnumed.117.193268
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Programmed Cell Death Ligand 1: Impact of Protein Concentration on Distribution of Anti-PD-L1 SPECT Agents in an Immunocompetent Murine Model of Melanoma

Abstract: Programmed cell death ligand 1 (PD-L1) is part of an immune checkpoint system that is essential for preventing autoimmunity and cancer. Recent approaches in immunotherapy that target immune checkpoints have shown great promise in a variety of cancers, including metastatic melanoma. The use of targeted molecular imaging would help identify patients who will best respond to anti-PD-L1 treatment while potentially providing key information to limit immune-related adverse effects. Recently, we developed an antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 27 publications
6
58
0
Order By: Relevance
“…In this respect, binding to PD-L1-expressing cells in blood or other tissue may prevent antibody extravasation and accumulation at the site of the tumor. 13 , 14 Moreover, lack of tumor-selectivity appears to result in generalized activation of antigen-experienced T cells, including functionally silenced auto-reactive T cells. The latter aspect is evidenced by the frequent occurrence of severe autoimmune-related adverse events during and after treatment with PD-L1-blocking antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, binding to PD-L1-expressing cells in blood or other tissue may prevent antibody extravasation and accumulation at the site of the tumor. 13 , 14 Moreover, lack of tumor-selectivity appears to result in generalized activation of antigen-experienced T cells, including functionally silenced auto-reactive T cells. The latter aspect is evidenced by the frequent occurrence of severe autoimmune-related adverse events during and after treatment with PD-L1-blocking antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies showed that immuno‐PET monitoring of CD8+ T cells could serve as a predictive and prognostic biomarker for immune checkpoint therapy . Currently, effective efforts are underway to define PD‐L1 or PD‐1 expression using noninvasive molecular probes, of which a large number of studies focused on the feasibility of antibody‐based tracers in immunotherapy …”
Section: Imaging Biomarkers For Immune Checkpoint Therapymentioning
confidence: 99%
“…For instance, Natarajan et al developed 89 Zr‐keytruda and 64 Cu‐keytruda to visualize PD‐1 expression on human tumor infiltrating lymphocytes within tumors and lymphoid tissues . With regard to SPECT/CT‐based molecular imaging, several studies showed the capacity of 111 In labeled anti‐PD‐L1 antibodies for imaging PD‐L1 expression in triple‐negative breast cancer (TNBC) and NSCLC . Furthermore, Pang et al demonstrated that 131 I‐PD‐L1 monoclonal antibody (mAb) could be a potential tool for noninvasively visualizing PD‐L1 expression in primary tumors and metastases .…”
Section: Imaging Biomarkers For Immune Checkpoint Therapymentioning
confidence: 99%
See 2 more Smart Citations